The Relationship Between Gender and Communication Apprehension among Administrative Staff in Universiti Utara Malaysia - Muhammad Fadhli Mohd Diah; Nadia Abd Rahman; Salmi Hussain; Nasyrul Hakim Mohd Zahir; Juwati Abdullah (Javanologi: International Journal of Javanese Studies, 2023)
ABSTRACT This research addresses issues on communication apprehension in using English language among administrative staff (grade 19) at Universiti Utara Malaysia (UUM). The notion of communication apprehension in this context is their anxiety in executing language tasks in terms of: group discussion, meeting, interpersonal and public speaking by using English language as medium. The objectives of this research are to identify the level of anxiety in using English language among the administrative staff and to find the correlation of communication apprehension with academic background and also gender. The methodology used in this research is using a quantitative approach and applying an instrument called Personal Report of Communication Apprehension (PRCA-24) developed by James C. McCroskey (1982) in order to assess the level of anxiety in using English language. The findings revealed that have female experience lower CA than the male participants.Keywords: Communication Apprehension, English, PRCA-24, Administrative Staff, Gender